Study of the Antioxidative Effects of Bombyx mori Silk Sericin in Cultures of Murine Retinal Photoreceptor Cells - Shuko Suzuki; Onur Sakiragaoglu; Traian V. Chirila (Molecules, 2022)
The availability of natural substances able to fulfill the role of antioxidants in a physiologic environment is important for the development of therapies against diseases associated with excessive production of reactive oxygen species and ensuing oxidative stress. Antioxidant properties have been reported episodically for sericin, a proteinaceous constituent of the silk thread in the cocoons generated by the larvae of the Lepidoptera order. We investigated the sericin fractions isolated from the cocoons spun by the domesticated (Bombyx mori) silkworm. Three fractions were isolated and evaluated, including two peptidoid fractions, the crude sericin and the purified (dialyzed) sericin, and the non-peptidoid methanolic extract of the crude fraction. When subjected to Trolox equivalent antioxidant capacity (TEAC) assay, the extract showed much higher antioxidant capacity as compared to the crude or purified sericin fractions. The three fractions were also evaluated in cultures of murine retinal photoreceptor cells (661 W), a cell line that is highly susceptible to oxidants and is crucially involved in the retinopathies primarily caused by oxidative stress. The extract displayed a significant dose-dependent protective effect on the cultured cells exposed to hydrogen peroxide. In identical conditions, the crude sericin showed a certain level of antioxidative activity at a higher concentration, while the purified sericin did not show any activity. We concluded that the non-peptidoid components accompanying sericin were chiefly responsible for the previously reported antioxidant capacity associated with sericin fractions, a conclusion supported by the qualitative detection of flavonoids in the extract but not in the purified sericin fraction.